2014
DOI: 10.1155/2014/637052
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Effect of Tube Rows on the Heat Transfer Characteristic of Dimpled Fin

Abstract: The dimpled fin has excellent heat transfer performance and has attracted a lot of attention to apply on the fin and tube heat exchanger. A study presents to investigate the effects of number of tube rows on the air-side heat transfer characteristics of dimpled fin for velocity ranging from 1 to 3 m/s. The /Δ and /((Δ × )) are used to evaluate the heat transfer performance of the heat exchanger. The results show that the dimpled arrangement can change the mainstream direction, increase the disturbance, and enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Figure 2. Plate-and-tube heat exchanger, studied by CFD methods in [6]: 1 -dimpled fin Its thermal and hydraulic characteristics were investigated by CFD methods in [6].…”
Section: Proposal Of Continuous Fins Dimpling Usage For Improvement Omentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2. Plate-and-tube heat exchanger, studied by CFD methods in [6]: 1 -dimpled fin Its thermal and hydraulic characteristics were investigated by CFD methods in [6].…”
Section: Proposal Of Continuous Fins Dimpling Usage For Improvement Omentioning
confidence: 99%
“…But this work does not attempt to determine the optimal configuration of the mutual arrangement of the recesses, protrusions and edges, but noted their positive mutual influence on heat transfer in a channel. Some results of numerical study heat transfer and hydrodynamics of such heat exchanger obtained in [6] are shown in fig.5. For dimpled fins and a one row of tubes authors obtained Nu number depending on Re number for smooth and dimpled fins ( see fig.5).…”
Section: Proposal Of Continuous Fins Dimpling Usage For Improvement Omentioning
confidence: 99%
“…Similarly, others also investigated the flow and heat transfer of dimple channels, effects of bleed holes and nanofluids flow in dimpled channels (Qu et al, 2013;Shen et al, 2013;Sinha and Srivastava, 2017). Furthermore, heat transfer characteristics of dimple protrusion (Chen et al, 2014;Li et al, 2014;Liu et al, 2015;Shen et al, 2017;Li et al, 2016;Zheng et al, 2016) and dimple fin (Chang et al, 2017;Wei et al, 2016;Wu et al, 2014;Luo et al, 2015;Park et al, 2016;Fan and Yin, 2008) were also widely studied. Based on above backgrounds, these works all showed the positive effects of dimples by observing the importance of geometrical parameters and flow properties.…”
Section: Introductionmentioning
confidence: 99%